Mechanisms regulating adult neurogenesis in the hypothalamus using a genetic inducible-approach to label and optogenetically stimulate hypothalamic neural progenitors - Peswani, Rahul Lekhraj (2019)
Adult neurogenesis is defined as the generation of newborn functional neurons during adulthood. In addition to the canonical neurogenic niches in the hippocampus and lateral ventricles, the hypothalamus has recently been shown to exhibit adult neurogenesis. We first aimed to elucidate the regulation of adult hypothalamic neurogenesis by investigating the effect of novel external factors on hypothalamic cell proliferation: physical exercise, antidepressant (fluoxetine) and non- nutritive artificial sweetener, acesulfame-K (Ace-K). Short/mid-term (14-21 days) exposure of Ace-K, but not physical exercise or fluoxetine induced changes in the number of newly generated cells: a decrease in the dorsomedial nucleus at 7 days, and an increase in the ventromedial nucleus at 14 days. Next, although the exact identity of the neural stem/progenitor cells underlying hypothalamic neurogenesis is still under debate, tanycytes have been proposed as an attractive candidate. However, the cellular/molecular mechanism underlying their neurogenic role has yet to be elucidated. We hypothesized that the intracellular calcium signalling induced by their chemosensory role might also be linked to their neurogenic role. We used a Cre-inducible genetic- labelling approach (nestin-CreERT2:Rosa-YFP) to characterize hypothalamic nestin+ stem/progenitor cells as part of validating this strategy for in vivo optogenetic stimulation of tanycytes. The vast majority (97%) of labelled cells were found at the ependymal layer and identified as tanycytes and ependymocytes. A small percentage of parenchymal cells were also labelled, which resembled neuronal and glial cells. Over time, an increasing trend in parenchymal labelled cells was seen, indicating a slow basal rate of neurogenesis. We then generated a transgenic line (nestin-CreERT2:Rosa-ChR2-YFP) in which tanycytes expressed Channelrhodopsin-2. Optogenetic stimulation of tanycytes in mouse brain slices induced strong and reproducible intracellular calcium waves. In vivo optogenetic stimulation of hypothalamic cells specified by nestin expression induced an increase in newly generated cells in close proximity to optically-responsive tanycytes, whilst long-term optogenetic stimulation indicated an increasing trend in labelled tanycytes and hypothalamic neurons. We have thus, successfully generated an optogenetic mouse model and validated its use in the hypothalamus to stimulate tanycytes (and potentially other putative neural progenitors). Although we cannot determine if the observed effects were solely due to tanycyte stimulation, we speculate that adult hypothalamic neurogenesis is regulated slowly, requiring long-term stimulation (optogenetically or by external/environmental stimuli). Further investigation using this optogenetic approach would prove helpful in elucidating the role/contribution of tanycytes in the regulation of adult hypothalamic neurogenesis.